Record of the giant imperial Purlisa gigantea distant, 1881 (Lepidoptera: Lycaenidae) in Dempo Mountain, South Sumatra, Indonesia - Iqbal, Muhammad; Aprilia, I; Pormansyah; Pragustiandi, G; Saputra, R.F.; Setiawan, A; Yustian, I (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
A specimen of the Giant Imperial Purlisa gigantea Distant, 1881 (Lepidoptera: Lycaenidae) was collected on 5th February 2020 from lower Dempo Mountain, South Sumatra Province, Indonesia and preserved. This finding is likely to represent the first record of P. gigantea in Dempo Mountain, South Sumatra Province, Indonesia.